2021
DOI: 10.1159/000519182
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppression in Glomerular Diseases: Implications for SARS-CoV-2 Vaccines and COVID-19

Abstract: <b><i>Background:</i></b> Glomerular diseases (GD) are chronic conditions that often involve immune dysfunction and require immunosuppressive therapy (IST) to control underlying pathogenesis. Unfortunately, such diseases appear to heighten risks of severe outcomes in COVID-19 and predispose to other infections that may be life-threatening. Thus, averting preventable infections is imperative in GD patients. <b><i>Summary:</i></b> The advent of vaccines demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…Several potential risk factors for failed seroconversion have been suggested, immunosuppression and its intensity in the post-transplant period being the most important [44]. The number of vaccine doses received also influences the development of an immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Several potential risk factors for failed seroconversion have been suggested, immunosuppression and its intensity in the post-transplant period being the most important [44]. The number of vaccine doses received also influences the development of an immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Immunosuppressive treatment of rheumatic diseases is associated with reduced immunity to mRNA vaccines ( 5 , 6 ) and poor outcomes ( 7 ). Although there are several reports on seroconversion against SARS-CoV-2 vaccines in patients with kidney disease receiving immunosuppressive treatment ( 8 , 9 ), few studies have compared the degree of serial humoral immune responses among different treatment regimens. The objective of this study was to estimate the humoral immune response, as measured by the immunoglobulin G (IgG) levels, against the SARS-CoV-2 spike receptor-binding domain (RBD-IgG) following the third mRNA coronavirus disease 2019 (COVID-19) vaccination in patients with kidney disease who received immunosuppressive treatment.…”
Section: Introductionmentioning
confidence: 99%
“…During the ongoing COVID-19 pandemic, accrued data worldwide across the socio-geographic spectrum has convincingly shown that COVID-19 infection-related morbidity and mortality risks can be amplified in kidney disease and immunocompromised hosts [ 6 , 7 ]. Thus, leading expert opinion had empirically recommended COVID-19 vaccination for patients with immune-mediated kidney diseases [ 8 ], despite limited published data regarding vaccine efficacy in glomerulonephritides treated with immunosuppressants [ 9 ]. However, the lack of trial safety data in glomerulonephritides and reports of IgA nephropathy flares after vaccination that emerged in early 2021 [ 10 , 11 , 12 ] have led to calls for nephrologists to advocate COVID-19 vaccination but counsel patients regarding a small risk of relapsing disease for up to one month after the second dose and to monitor for symptoms suggestive of relapse [ 11 ].…”
Section: Introductionmentioning
confidence: 99%